Alexithymia in diabetes patients: its relationship with perceived social support and glycaemic control. Issue 17 (17th October 2021) - Celik, Selda; Taskin Yilmaz, Feride; Yurtsever Celik, Sultan; Anataca, Gulden; Bulbul, Elif
Abstract: Aim and Objective: This study was conducted to assess whether there is an association between alexithymia in patients with diabetes and the levels of perceived social support and glycaemic control. Background: In the literature, whether inadequate perceived social support is a cause or effect of alexithymia has also not been clearly explained. It is stated that it is difficult to determine from where these contradictions arise, and there is a need for more studies on this topic. Method: This cross‐sectional and correlational study included 537 patients with type I and type 2 diabetes. The data were collected using a Patient Information Form including the patient's HbA1c value that reflected their glycaemic control level, the Toronto Alexithymia Scale and the Multidimensional Scale of Perceived Social Support. The study was reported according to the STROBE Declaration. Results: Among the patients with diabetes, 63.9% showed signs of alexithymia. Alexithymia had a negative relationship with perceived social support and a positive relationship with HbA1c. Additionally, it was determined that the patients who showed signs of alexithymia had lower levels of perceived social support in comparison with those who did not show such signs, whereas the HbA1c levels of the former were also higher than those of the latter. Moreover, it was found that the duration of the disease, HbA1c levels and levels of perceived social support from family and a significant other explained 30% of the total variance in the level of alexithymia. Conclusion: Alexithymia was seen prevalently among the patients with diabetes, and it was associated with a reduced level of perceived social support and weak glycaemic control. Relevance to clinical practice: It is recommended to provide patients with psychosocial support in the scope of holistic care and include the individuals who provide care for and support the patient in the patient's management of the disease.